Vai[ecikasktra : a translation - KaGga(Bda.s; KaGga(Bda.s; Candrga(Bnanda.s; Jambkvijaya, Muni.; Moise, Ionut, 1982-; Thite, Ganesh Umakant (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book introduces readers to Indian philosophy by presenting the first integral English translation of Vai[ecikasktra with the earliest extant commentary of Candrga(Bnanda on the old aphorisms of Vai[ecika school of Indian philosophy. The book offers a comprehensive description of the fundamental categories of ontology and metaphysics, among which the category of 'particularity' (vi[eca) plays a major role in the 'problem of individuation' of 'substance' and 'nature' in both Indian and Western metaphysics. The book should be read primarily in relation to Aristotle's Categories and is structured in three parts. Part 1 contains a general introduction to Indian philosophy and the Vai[ecika system. Part 2 is a textual-philological discussion on the commentary itself, since its first publication in 1961 by Muni Jambkvijayaji up until the present day. Part 3 is a philosophical translation that reads Vai[ecika in the global context of Comparative Philosophy and makes the text accessible to all philosophy readers interested in ontology and metaphysics. A new reference work and a fundamental introduction to anyone interested in Indian and Comparative Philosophy, this book will be of interest to academics and students in the field of Classical Studies, Modern Philosophy and Asian Religions and Philosophies"--s
1. Introduction to Indian Philosophy and Vai[ecika -- 2. Sources and Resources on Vai[ecikasktra -- 3. Vai[ecikasktra: Transliteration and Translation -- Appendixes -- Bibliography -- Index on Sanskrit terms with Glossary.
Keywords: KaGga(Bda.s; Aristotle; Vai[ecika -- Early works to 1800.; Ontology -- Religious aspects -- Hinduism; Metaphysics; Philosophy, Ancient; SOCIAL SCIENCE / Ethnic Studies / General